Lesson from the emergence, spread and decline of Dickeya solani, the virulent potato blackleg and soft rot bacterial pathogen in Finland - Degefu, Yeshitila (Wiley-Blackwell, 2024)
The threat of emerging plant diseases has become more frequent as global warming and international trade are increasing. Blackleg and soft rot of potatoes caused by the group of bacteria in the family Pectobacteriaceae and the genera Dickeya and Pectobacterium are important diseases causing economic losses globally. In the European Union, they are regulated non-quarantine pests. Five species are commonly known to cause blackleg symptoms on potatoes indistinguishable from each other. For decades, P. atrosepticum has been the classic seed potato bacterial pathogen in cool temperate climates of Europe and North America, causing blackleg disease. However, recently several new species, unknown in Northern Europe, have emerged as virulent pathogens. One of these species is D. solani. In Finland, D. solani was first found in 2004 and has been the cause of major outbreaks of blackleg in Finland for more than a decade. Currently, its incidence has declined significantly because of a stringent, concerted engagement strategy adopted to combat the pathogen that is described in detail in this article. This strategy implemented in Finland could serve as a model system to combat other emerging and re-emerging species of Dickeya and Pectobacterium and serve as useful support information for the formulation of a policy framework for the management of emerging plant health risks.
Keywords: blackleg; Dickeya solani; emerging pathogens; Pectobacteriaceae; soft rot; zero-tolerance